Ethical issues raised by cluster randomised trials conducted in low-resource settings: identifying gaps in the Ottawa Statement through an analysis of the PURE Malawi trial. Issue 6 (12th June 2019) - Mtande, Tiwonge K; Weijer, Charles; Hosseinipour, Mina C; Taljaard, Monica; Matoga, Mitch; Goldstein, Cory E; Nyambalo, Billy; Rosenberg, Nora E
Abstract : The increasing use of cluster randomised trials in low-resource settings raises unique ethical issues. The Ottawa Statement on the Ethical Design and Conduct of Cluster Randomised Trials is the first international ethical guidance document specific to cluster trials, but it is unknown if it adequately addresses issues in low-resource settings. In this paper, we seek to identify any gaps in the Ottawa Statement relevant to cluster trials conducted in low-resource settings. Our method is (1) to analyse a prototypical cluster trial conducted in a low-resource setting ( PURE Malawi trial ) with the Ottawa Statement ; (2) to identify ethical issues in the design or conduct of the trial not captured adequately and (3) to make recommendations for issues needing attention in forthcoming revisions to the Ottawa Statement . Our analysis identified six ethical aspects of cluster randomised trials in low-resource settings that require further guidance. The forthcoming revision of the Ottawa Statement should provide additional guidance on these issues: (1) streamlining research ethics committee review for collaborating investigators who are affiliated with other institutions; (2) the classification of lay health workers who deliver study interventions as health providers or research participants; (3) the dilemma experienced by investigators when national standards seem to prohibit waivers of consent; (4) the timing of gatekeeper engagement, particularly when researchers face funding constraints; (5) providing ancillary care in health services or implementation trials when a routine care control arm is known to fall below national standards and (6) defining vulnerable participants needing protection in low-resource settings.